Sinus Floor Elevation with Modified Crestal Approach and Single Loaded Short Implants: A Case Report with 4 Years of Follow-Up - Michele Perelli; Roberto Abundo; Giuseppe Corrente; Carlo Saccone; Paolo G. Arduino (Hindawi Limited, 2017)
Tooth extraction is usually followed by bone reduction. In the maxillary posterior region, this remodelling combined with sinus pneumatisation and periodontal defects may lead to a reduced basal bone height available for implant placement. Sinus floor elevation can be performed with different surgical techniques. Crestal approach has demonstrated to be effective, less invasive, and associated with a reduced morbidity. This article reports a modified sinus floor elevation by means of rotary, noncutting instruments, addition of xenograft, and 2 short-threaded implant placements. The aim of the study was to evaluate the implant's success and intrasinus radiographical bone gain after 4 years of functional loading. The premolar implant site presented a starting basal bone height of 6 mm, while the molar site was of 2 mm. In the first surgical step, sinus floor elevation was performed mesially and the implant was inserted, and distally only sinus floor elevation was performed. After 6 months, the mesial implant was uncovered and the second implant was inserted; 4 months later, the second fixture was uncovered, and both fixtures were loaded with single provisional screw-retained crowns and later with single screw-retained porcelain fused to metal crowns. Implants integrated successfully, and crestal bone remodelling did not exceed the smooth collar. Bone gain was 3 mm for the mesial implant and more than 5 mm for the distal one.